Reform of Labour Protection Standards in the Process of Ukraine’s Integration in Europe - DENYSIUK, MARIIA; DEREVYANKO, MARYNA; ZELENSKY, VITALIY; KOSTIENNIKOV, DMYTRO (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The process of integration of Ukraine into the european community implies the adaptation of the legal framework, as well as important transformations of the social relations established in its population. The study demonstrates the most acute aspects of normative support for labor protection in Ukraine and presents possible ways of reforming the legislation based on the successful experience of the EU countries. The conceptual basis of the reformed legislation of Ukraine should be the protection of the rights of employees, as these rights are most often violated. RESUMEN El proceso de integración de Ucrania en la comunidad europea implica la adaptación del marco legal, así como importantes transformaciones de las relaciones sociales establecidas en su población. El estudio demuestra los aspectos más agudos del apoyo normativo a la protección laboral en Ucrania y presenta posibles formas de reformar la legislación basándose en la exitosa experiencia de los países de la UE. La base conceptual de la legislación reformada de Ucrania debe ser la protección de los derechos de los empleados, ya que estos derechos se infringen con mayor frecuencia.